The Influence Of Electronic Word Of Mouth (eWOM), Celebrity Worship, And Paylater Features On Purchase Decisions With Consumptive Behavior As An Intervening Variable Among Korean Pop Fans - Hafizhah Zahra Farhani; Rusdarti; Prihandono, Dorojatun (Universitas Negeri Semarang, 2025)
This study investigates the determinants of purchasing decisions among teenage Korean-pop fans in Semarang City, highlighting the role of consumer behavior as a mediating variable. Understanding this phenomenon is increasingly important as the rapid growth of fan-based consumption has become a significant driver of youth spending patterns and a relevant topic in contemporary consumer behavior research. The variables examined include electronic word of mouth, celebrity worship, and pay later features. A quantitative approach was employed with 100 respondents selected through consecutive sampling to capture active consumers within a specific time frame. Data were collected using validated and reliable questionnaires and analyzed using multiple linear regression and the Sobel test, methods deemed appropriate for identifying both direct and mediating effects. The findings show that electronic word of mouth, celebrity worship, and pay later features positively and significantly influence purchasing decisions, with consumer behavior serving as an effective mediating factor. Practically, the findings guide marketers in targeting youth through digital and financial features, while scientifically they advance a mediation model that integrates psychological and financial determinants of fan-based purchasing behavior.